Glycol assisted efficient conversion of CO2 captured from air to methanol with a heterogeneous Cu/ZnO/Al2O3 catalyst. Issue 54 (December 2021) - Sen, Raktim; Koch, Christopher J.; Galvan, Vicente; Entesari, Nazanin; Goeppert, Alain; Prakash, G.K. Surya
Graphical abstract: Highlights: First example of integrated CO2 capture and conversion to methanol using a commercial Cu/ZnO/Al2 O3 catalyst is demonstrated. An efficient and recyclable alcohol assisted system was developed for CO2 hydrogenation with methanol yields up to 90%. A 120% increase in methanol yield was achieved using ethylene glycol as the solvent. A renewable methanol synthesis is reported using the combination of heterogeneous catalysis and air as the carbon source. Abstract: A highly effective liquid phase system for hydrogenation of CO2 to methanol using a heterogeneous Cu/ZnO/Al2 O3 catalyst under batch conditions was developed. Among the screened solvents, glycols were found to have a marked promoting effect on methanol formation at a relatively low temperature range of 170–200 °C using molecular H2 . Relative to the solventless system, ethylene glycol enhanced the CO2 conversion values by up to 120% which is close to the calculated equilibrium limit. CH3 OH yields of up to 90% were achieved. The catalyst was remarkably stable and recyclable over multiple hydrogenation cycles. Furthermore, CO2 captured by alkali hydroxides as well as amines were successfully hydrogenated to CH3 OH with the Cu/ZnO/Al2 O3 catalyst for the first time with >90% yields. The catalytic process and the plausible reaction pathways were evaluated by control experiments, which suggest that the hydrogenation in the presence of an alcohol proceeds through the formation of formate ester as an intermediate. Finally, the integration of direct air capture (DAC) and hydrogenation of CO2 was demonstrated efficiently as a novel methanol synthesis process using the combination of heterogeneous catalysis and air as a renewable carbon source. Such scalable processes have considerable potential for synthesis of renewable methanol in an efficient and relatively cost-effective approach.